Parent–Child Interaction Therapy with Toddlers in a community‐based setting: Improvements in parenting behavior, emotional availability, child behavior, and attachment. Issue 4 (26th June 2020) - Kohlhoff, Jane; Morgan, Susan; Briggs, Nancy; Egan, Ryan; Niec, Larissa
ABSTRACT: Parent–Child Interaction Therapy with Toddlers (PCIT‐T) is a new attachment‐based parenting intervention designed to meet the needs of children aged 12–24 months presenting with challenging behaviors. This study examined outcomes of the first phase of PCIT‐T, Child Directed Interaction–Toddler (CDI‐T), 4‐months post treatment. Participants were 56 toddlers (Child M age = 19.13 months) referred to receive CDI‐T over an 8‐week period at an Australian community‐based child behavior treatment clinic for treatment of difficult toddler behaviors. Participants completed questionnaires and observational measures at baseline (Time 1), post‐treatment (Time 2), and 4‐month follow‐up (Time 3). At both Time 2 and Time 3, there were statistically significant increases in observed positive parenting skills and emotional availability and decreases in negative parenting behaviors and child noncompliance. There were also significant improvements in parent‐reported child externalizing and internalizing behaviors, parental stress, and maternal depression. There was a pattern of a shift away from attachment insecurity and attachment disorganization. Results suggest that the CDI‐T phase of PCIT‐T is a promising intervention for toddlers presenting with behavioral issues. Future studies should be conducted to assess efficacy in other settings, using larger samples and utilizing randomized controlled designs. RESUMEN: La terapia de interacción progenitor‐niño con niños pequeñitos (PCIT‐T) es una nueva intervención de crianza con base en la afectividad y diseñada para cubrir las necesidades de niños de edad de 12 a 24 meses que enfrentan retos de comportamiento. Este estudio examinó los resultados de la primera fase de PCIT‐T, Interacción Dirigida del Niño – Niño Pequeñito (CDI‐T), 4 meses después del tratamiento. Participaron 56 niños pequeñitos (Edad promedio del niño = 19.13 meses) que habían sido referidos para recibir el CDI‐T en un período de 8 semanas en una clínica en Australia con base comunitaria de tratamiento de comportamiento del niño, dedicada al tratamiento de comportamientos difíciles de niños pequeñitos. Los participantes completaron cuestionarios y medidas de observación al momento básico (Primer momento), posteriormente al tratamiento (Segundo momento) y en el seguimiento a los 4 meses (Tercer momento). Tanto en el momento segundo como en el tercero, se dieron mejorías estadísticamente significativas en cuanto a las observadas habilidades positivas de crianza y la disponibilidad emocional y disminuciones en cuanto a las conductas de crianza negativas y la falta de obediencia del niño. También se dieron mejorías significativas en los comportamientos de externalización e internalización del niño según el reporte del progenitor, el estrés de los padres y la depresión materna. Se dio un patrón de alejarse de la inseguridad de la afectividad y la desorganización de la afectividad. Los resultados sugieren que la fase CDI‐T del PCIT‐T es una intervención prometedora para niños pequeñitos que presentan asuntos de comportamiento. Futuros estudios deben llevarse a cabo para evaluar la efectividad en otros escenarios, usando grupos muestras más grandes y utilizando diseños de control al azar. RÉSUMÉ: La thérapie d'interaction parent‐enfant avec un jeune enfant (en anglais Parent‐child interaction therapy with Toddlers, soit PCIT‐T) est une nouvelle intervention de parentage basée sur l'attachement, conçue afin de remplir les besoins d'enfants âgés de 12 à 24 mois qui présentent des comportements difficiles. Cette étude a examiné les résultats de la première phase de PCIT‐T, l'Interaction Dirigée vers l'Enfant – Petit Enfant (Child Directed Interaction – Toddler, soit CDI‐T), à 4 mois après le traitement. Les participants ont consisté en 56 jeunes enfants (âgeM de l'Enfant = 19, 13 mois) envoyés consulter afin de recevoir une CDI‐T sur une période de 8 semaines dans une clinique de traitement du comportement de l'enfant communautaire en Australie, spécialisé dans le traitement de comportements difficiles de jeunes enfants. Les participants ont rempli des questionnaires et des mesures d'observation au niveau de référence (Temps 1), après le traitement (Temps 2) et au suivi de 4 mois (Temps 3). A la fois au Temps 2 et 3 on a noté des augmentations statistiquement significatives dans les compétences positives observées de parentage et la disponibilité émotionnelle ainsi que des baisses dans les comportements négatifs de parentage et le refus d'obéir. On a aussi noté des améliorations importantes dans l'externalisation de l'enfant rapportée par le parent et les comportements d'internalisation, le stress parental et la dépression maternelle. On a observé une tendance se détachant de l'insécurité de l'attachement et de la désorganisation de l'attachement. Les résultats suggèrent que la phases CDI‐T de la PCIT‐T est une intervention prometteuse pour les jeunes enfants présentant des problèmes de comportement. Des études futures devraient être faites afin d'évaluer l'efficacité d'autres contextes, en utilisant des échantillons plus larges et en utilisant des plans d'étude contrôlées randomisées. ZUSAMMENFASSUNG: Eltern‐Kind‐Interaktionstherapie mit Kleinkindern in einem gemeindebasierten Setting: Verbesserungen in der emotionalen Verfügbarkeit, im kindlichen Verhalten und in der Bindung Die Eltern‐Kind‐Interaktionstherapie mit Kleinkindern (Parent‐child interaction therapy with Toddlers; PCIT‐T) ist eine neue bindungsbasierte Elternkompetenz‐Intervention, die auf die Bedürfnisse von Kindern im Alter von 12 bis 24 Monaten mit herausfordernden Verhaltensweisen zugeschnitten ist. Die vorliegende Studie untersuchte die Ergebnisse der ersten Phase von PCIT‐T, an das Kind gerichtete Interaktion – Kleinkind (Child Directed Interaction – Toddler: CDI‐T), 4 Monate nach der Behandlung. 56 Kleinkinder (mittleres Alter = 19, 13 Monate), die aufgrund von Verhaltensstörungen über einen Zeitraum von 8 Wochen an eine gemeindebasierte Klinik in Australien verwiesen worden waren, um die CDI‐T Intervention zu erhalten, nahmen an der Studie teil. Die Datenerhebung erfolgte zu Studienbeginn (Messzeitpunkt 1), nach der Behandlung (Messzeitpunkt 2) und nach 4 Monaten (Messzeitpunkt 3) durch Fragebögen und Beobachtungsmaße. Sowohl zum Messzeitpunkt 2 als auch zum Messzeitpunkt 3 gab es statistisch signifikante Steigerungen in der beobachteten Elternkompetenz und in der emotionalen Verfügbarkeit sowie Abnahmen im negativen Elternverhalten und im unbeteiligten Verhalten der Kinder. Es gab auch signifikante Verbesserungen bei dem von Eltern berichteten kindlichen Externalisierungs‐ und Internalisierungsverhalten, beim elterlichen Stress und bei der mütterlichen Depressivität. Außerdem gab es eine Tendenz hin zur Abkehr von Bindungsunsicherheit und desorganisierter Bindungen. Die Ergebnisse legen nahe, dass die CDI‐T‐Phase von PCIT‐T eine vielversprechende Intervention für Kleinkinder mit Verhaltensproblemen ist. Zukünftige Studien sollten durchgeführt werden, um die Wirksamkeit in anderen Settings und unter Verwendung größerer Stichproben sowie randomisierter kontrollierter Designs zu bewerten. 抄録: 地域における幼児との親子相互交流療法:情緒的応答性、幼児の行動及びアタッチメントの向上 幼児との親子相互交流療法(PCIT‐T)は、挑戦的行動を示す12‐24ヶ月児の要求に応えることを目的とし、アタッチメント理論を基盤とした養育への介入のものである。本研究は、PCIT‐Tの第一段階である 子ども指向相互交流−幼児 (CDI‐T)の治療後4ヶ月たった時点において、結果を考察した。参加者は、困難な幼児行動の治療を行うために、オーストラリアの地域を基盤とした幼児行動治療クリニックに8週間のCDI‐Tを受けるために紹介された56人の幼児(子ども平均19.13ヶ月)であった。参加者は、開始前(Time 1)と治療直後(Time 2)、4ヶ月後のフォローアップ時(Time 3)に、質問紙と観察測定を完了した。Time 2とTime 3の両方に、 観察された肯定的な養育スキルと情緒的応答性において統計的に有意な増加があり、否定的な養育スキルと子どもの不服従において有意な減少があった。また、 親の報告による子どもの外在化・内在化行動、親自身のストレス及び母親の抑鬱に関しては有意な改善があった。アタッチメントの不安型と無秩序型から変化していくという傾向があった。結果は、PCIT‐TにおけるCDI‐T段階というものが、 行動に課題のある幼児にとって有望な介入であると示唆される。今後は、別の設定において、より多くの標本を使用したり、無作為化対照デザインを活用するなどして、効果を評価する更なる研究が必要であろう。 摘要: 针对幼儿的亲子互动疗法 (PCIT‐T) 是一种基于依恋的新型育儿干预措施, 旨在满足表现出挑战性行为的12–24个月龄儿童的需要。本研究检验了治疗后4个月的PCIT‐T第一阶段——以幼儿为主导的干预疗法 (CDI‐T) 的疗效。研究参与者为56名幼儿 (平均月龄为19.13), 他们在专治困难幼儿行为的澳大利亚社区儿童行为治疗诊所接受了为期8周的CDI‐T治疗。参与者分别在治疗起始阶段 (时间1) 、治疗后 (时间2) 和4个月的随访阶段 (时间3) 三个时间点完成了调查问卷和观测评估。在时间2和时间3两个阶段, 我们观测到父母的积极育儿技能和情感回馈度在统计学上均显著增加, 而消极育儿行为和儿童不顺从性在统计学上均显著减少。父母报告的儿童外化和内化行为、育儿压力和母亲抑郁症也都有显著改善。 从而得到一种摆脱不安全型依恋和混乱型依恋的方式。结果表明, PCIT‐T的CDI‐T阶段对于出现行为问题的幼儿是一种有希望的干预疗法。未来的研究应该在其他环境下, 使用更大的样本并利用随机对照设计来评估疗效。 ملخص: العلاج بالتفاعل بين الوالدين والطفل مع الأطفال الصغار في بيئة مجتمعية: التحسينات في التوافر العاطفي وسلوك الأطفال والتعلق . الملخص العلاج بالتفاعل بين الوالدين والطفل مع الأطفال الصغار (PCIT‐T) هو تدخل أبوي جديد قائم على التعلق مصمم لتلبية احتياجات الأطفال الذين تتراوح أعمارهم بين 12–24 شهرًا الذين يعانون من سلوكيات صعبة. تناولت هذه الدراسة نتائج المرحلة الأولى من PCIT‐T، والتفاعل الموجه للأطفال (CDI‐T)، و4 أشهر من العلاج. وكان المشاركون 56 طفلاً صغيراً (معدل عمر = 19.13 شهراً) المشار إليهم في تلقي CDI‐T على مدى 8 أسابيع في عيادة علاج سلوك الأطفال المجتمعية الأسترالية لعلاج سلوكيات الأطفال الصعبة. وأكمل المشاركون استبيانات ومقاييس ملاحظة في بداية العلاج (الوقت 1)، وما بعد العلاج (الوقت 2)، والمتابعة لمدة 4 أشهر (الوقت 3). وفي كل من الوقت 2 والوقت 3، حدثت زيادات ذات دلالة إحصائية في مهارات الأبوة الإيجابية الملحوظة والتوافر العاطفي والانخفاض في السلوكيات الوالدية السلبية وعدم امتثال الأطفال. كما حدثت تحسينات كبيرة في السلوكيات الخارجية والداخلية للأطفال المبلغ عنها من الوالدين، والإجهاد الأبوي، والاكتئاب الأمومي. كان هناك نمط من التحول بعيدا عن انعدام أمن وعدم تنظيم التعلق. تشير النتائج إلى أن مرحلة التفاعل الموجه للأطفال من PCIT‐T هي تدخل واعد للأطفال الصغار الذين يظهرون مشكلات سلوكية. ويجب إجراء دراسات مستقبلية لتقييم الفعالية في بيئات أخرى، باستخدام عينات أكبر واستخدام تصاميم معشاة خاضعة للرقابة.